Eksistensi demokrasi Indonesia di tengah perubahan sosial dan digital - Yahya, Zacky (Maliki Interdisciplinary Journal, 2026)
Democracy in Indonesia continues to develop along with social changes and the rapid advancement of digital technology. The digital era has brought significant influences to society, especially in politics, communication, and public participation. Social media and the internet provide broader opportunities for people to express opinions, access information, and monitor government policies. This condition indicates that digital technology can strengthen democratic practices through information transparency and increased public participation, particularly among young generations. However, digital development also creates various challenges for the sustainability of democracy in Indonesia. The spread of hoaxes, hate speech, identity politics, and low levels of digital literacy have become threats that may trigger social division and reduce the quality of democracy. This study aims to analyze the existence of Indonesian democracy amid social and digital transformation and to understand the challenges and efforts needed to maintain democratic stability. The method used in this study is a qualitative descriptive approach by examining various social and digital phenomena occurring in society. The results show that Indonesian democracy still has a strong existence if society is able to use technology wisely, improve digital literacy, and uphold the values of Pancasila in national and state life.